PENGARUH KOMUNIKASI PENYULUHAN PERTANIAN TERHADAP KINERJA KELOMPOK TANI DI DESA KARANG TINOTO KECAMATAN RENGEL KABUPATEN TUBAN - Rozaq, Miftahul; Sudaryanto, Edy (Universitas 17 Agustus 1945 Surabaya, 2018)
The effectiveness of communication has an important role in the process of agriculturalextension activities. Effective communication in agricultural extension activities in confidence canimprove the performance of farmer groups to create the effectiveness of extension communication inneed of participation of the perpetrators of extension activities. This study aims to determine the effectof communication effectiveness of extension on the performance of farmer groups, and the influence ofextension participation on the effectiveness of extension communication that is done in Karang TinotoVillage, Rengel District, Tuban Regency. This research is done by using quantitative approach andusing survey method. Type of research is associative explanative. The research analysis used themoment and partial correlation product correlation test to know the relationship between thevariables. The sample in this study was 82 samples, determining the number of samples using slovinformula. The result of the research on product moment correlation test showed that there was apositive correlation of 0,583 and significant 0,000 between communication effectiveness counseling tofarmer group performance, there was positive relation 0,942 and significant 0.000 betweenparticipation counseling with effectiveness of communication of counseling. While the patelcorrelation test shows the participation of counseling very determine the effectiveness ofcommunication to the performance of farmer groups.Keywords: effectiveness of extension communication, farmer group performance, extensionparticipation